PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBASIS ASESMEN PORTOFOLIO TERHADAP HASIL BELAJAR SISWA PADA MATERI KOLOID - yudhi setiawan; lisa utami (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
The present study was encouraged by the low learning outcomes of students at MAN 1 Pekanbaru that were influenced by the lack of students’ participation during learning process and caused teacher-centered learning. This study was a quasi-experimental research with Pretest-Posttest Control Group design. It aimed at investigating the effect of implementing learning model “Guided Inquiry-Based Portfolio Assessment” on students’ chemistry learning outcomes in colloid topic at XI Grade of State Islamic Senior High School 1 Pekanbaru. Afterwards, the samples of this study were students of XI Science 2 class as an experimental class and XI Science 3 as a control class taken through simple random sampling from all students of XI Science classes in academic year 2015/2016 as population. In addition, the data was collected by using tests including homogeneity test as the preliminary data in the previous materials and pretests and posttests as the last data, documentation, and observation. Then, the data were analyzed by using t-test. As the result, it was obtained that tobtained =2.880 and ttable =2.000 in significance level 5%. Therefore, it showed that tobtained ≥ ttable so that Ho was rejected and Ha was accepted which indicated that there was an effect of implementing learning model “Guided Inquiry-Based Portfolio Assessment” on students’ chemistry learning outcomes in colloid topic at XI Grade of State Islamic Senior High School 1 Pekanbaru with influence coefficient 12.5%. Key words: 1. learning model “Guided Inquiry-Based Portfolio Assessment”, learning outcomes, colloid.